2016
DOI: 10.1186/s12885-016-2766-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of breast cancer molecular subtypes in routine clinical care: A large prospective cohort study

Abstract: BackgroundIn Germany, most breast cancer patients are treated in specialized breast cancer units (BCU), which are certified, and routinely monitored. Herein, we evaluate up-to-date oncological outcome of breast cancer (BC) molecular subtypes in routine clinical care of a specialized BCU.MethodsThe study was a prospectively single-center cohort study of 4102 female cases with primary, unilateral, non-metastatic breast cancer treated between 01 January 2003 and 31 December 2012. The five routinely used molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
107
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 41 publications
9
107
1
6
Order By: Relevance
“…A Korean study also demonstrated significant differences in local and [16]. However, the current study was unique in that we exclusively analyzed a study population who completed PORT, while prior investigations included a significant proportion of non-PORT patients [15][16][17][18]. In Haffty et al's analysis of 482 patients who underwent PORT after breastconserving surgery, the TN subtype (n = 117) was associated with a significantly lower 5-year distant metastasis-free rate (P = 0.002) but no significant differences in breast (P = 0.823) or nodal (P = 0.05) relapse-free rates [19].…”
Section: Discussionmentioning
confidence: 87%
“…A Korean study also demonstrated significant differences in local and [16]. However, the current study was unique in that we exclusively analyzed a study population who completed PORT, while prior investigations included a significant proportion of non-PORT patients [15][16][17][18]. In Haffty et al's analysis of 482 patients who underwent PORT after breastconserving surgery, the TN subtype (n = 117) was associated with a significantly lower 5-year distant metastasis-free rate (P = 0.002) but no significant differences in breast (P = 0.823) or nodal (P = 0.05) relapse-free rates [19].…”
Section: Discussionmentioning
confidence: 87%
“…The Luminal A subtype has the best prognosis followed by the other luminal subtypes [ 5,10,11 ]. However, studies of long http://eproofing.springer.com/journals/printpage.php?token=Rt1BrlQaTyuwuNxVhI_xPYwIUqIuNE6ZG1Tkr_jU9OeXCU3MBNMPbw 3/24 term survival have shown that luminal breast cancers can recur up to decades after primary diagnosis.…”
Section: Aq1mentioning
confidence: 99%
“…Another advantage of BCT is that it may allow the patients to avoid axillary dissection if they had a positive lymph node status after sentinel node biopsy and if they are treated according to the ACOSOG Z0011 criteria [51]. More than two-thirds of all primary breast cancer patients are nowadays treated with breast conservation in a routine clinical setting in a specialized breast unit in developed countries [1].…”
Section: Impacts In Counseling Patients In the Decision Of Bct Versusmentioning
confidence: 99%
“…LRR additionally depends on the immunohistochemical subtype, with the triple-negative type having the highest rates and the hormone receptor-positive and HER2-negative types having the lowest rates of LRR [27]. In a representative routine cohort from Germany with over 70% of the patients treated with BCT, LRR rates of 3.9% over 5 years were seen [1]. Thus, the rates of breast cancer recurrence after BCT are nowadays similar to the rates of local recurrence seen after mastectomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation